2002
DOI: 10.2527/2002.8061520x
|View full text |Cite
|
Sign up to set email alerts
|

Management of the female stimulus during semen collection and its association with libido re-establishment and semen characteristics of goats

Abstract: The effect of management of the female stimulus during semen collection and its association with libido re-establishment and the semen characteristics of sexually mature goats was evaluated. Eight 2-yr-old bucks were individually subjected to 12 weekly trials in which one of the following three treatments was applied alternately. In treatment one, each male performed two ejaculations on an estrus-induced, restrained doe and semen was collected with an artificial vagina (AV). In treatment two, males were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
3
6
1
1
Order By: Relevance
“…Most of the work to date on sexual stimulation in small ruminants has focused on restraining the male before semen collection or changing the female stimulus during repeated semen collection. This has been reported to be successful in goats through reducing reaction time (Prado et al, 2002(Prado et al, , 2003Silvestre et al, 2004) and increasing sperm output (Prado et al, 2003). In sheep, Thiery and Signoret (1978) demonstrated a shorter sexual reaction time in rams by changing the female stimulus, whereas Lezama et al, (2003) found no effect of changing the female stimulus on semen characteristics or interejaculation interval.…”
Section: Discussionmentioning
confidence: 90%
“…Most of the work to date on sexual stimulation in small ruminants has focused on restraining the male before semen collection or changing the female stimulus during repeated semen collection. This has been reported to be successful in goats through reducing reaction time (Prado et al, 2002(Prado et al, , 2003Silvestre et al, 2004) and increasing sperm output (Prado et al, 2003). In sheep, Thiery and Signoret (1978) demonstrated a shorter sexual reaction time in rams by changing the female stimulus, whereas Lezama et al, (2003) found no effect of changing the female stimulus on semen characteristics or interejaculation interval.…”
Section: Discussionmentioning
confidence: 90%
“…Other semen parameters values reported in bibliography in small ruminants were: volume 0.7-2 ml, concentration 2-5 × 10 9 spermatozoa/ml, motility 70-90% and a sperm abnormalities percentage 5-15% (Mann and Lutwac-Mann, 1981;Chemineau, 1986;Chemineau et al, 1991;Roca et al, 1992;Prado et al, 2002).…”
Section: Discussionmentioning
confidence: 97%
“…The reactions are considered by two criterions: i) Reaction time; measured as the amount of time between the first contact with the teaser ewe and the first false mount with the penis erected (Hoflack et al, 2006). ii) Refractory period; measured as the time taken between first ejaculate till the second false mount for second serving (Prado et al 2002). Each ram was allowed to mount with the stimulus ewe and following the time was recorded for the reaction time and then the refractory period.…”
Section: Assessment Of Libidomentioning
confidence: 99%